Cost savings analysis and toxicity audit of a bevacizumab dose rounding policy at a community cancer center. (January 2018) - Moore, Donald C; McVey, Gary Neal
Purpose: To evaluate the potential cost savings incurred from a policy to round doses of bevacizumab to the nearest vial size. Secondarily, to determine differences in rates of adverse events between patients who had their doses rounded up compared with those who had doses rounded down. Methods: This study is a retrospective chart review of all patients who received at least one rounded dose of bevacizumab over a period of 22 months. Doses of bevacizumab were calculated based on actual body weight. The calculated dose was then rounded to the nearest 400 or 100 mg vial size. The predicted effect on cost was calculated in US dollars for both the pre-rounded dose and the rounded dose. Adverse events including hypertension, proteinuria, and vascular events were compared between those that received a dose that was rounded up and those with a dose rounded down. Results: A total of 55 patients received at least one dose bevacizumab between 1 August 2014 and 31 May 2016. A total of 470 doses were administered. The estimated cost savings by rounding bevacizumab doses to the nearest 100 mg during the study time period was 164, 617.92. Patients receiving either a dose that was rounded up or rounded down to the nearest 100 mg experienced similar rates of adverse events. Conclusion: Dose rounding of bevacizumab to the nearest vial size resulted in significant cost savings and did not significantly impact the incidence of adverse events.